2010
DOI: 10.1007/s11274-010-0575-4
|View full text |Cite
|
Sign up to set email alerts
|

Different aspects of bacterial communication signals

Abstract: The communication or quorum-sensing signal molecules (QSSM) are specialized molecules used by numerous gram-negative bacterial pathogens of animals and plants to regulate or modulate bacterial virulence factor production. In plant-associated bacteria, genes encoding the production of these signal molecules, QSSMs, were discovered to be linked with the phenotype of bacterium, because mutation of these genes typically disrupts some behaviors of bacteria. There are other regulator genes which respond to the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 132 publications
(135 reference statements)
1
2
0
Order By: Relevance
“…In addition, various plant Es differently affect the biofilm formation, so the method of preparation of Es should also be considered. 36,102 The results obtained for H. orphanidis suggested that AEs expressed low anti-biofilm activity compared to MEs and EEs, which was in conformity with the results obtained for antimicrobial activity. Es obtained from aerial parts were more effective than Es obtained from roots in the suppression of biofilm formation (Table 8).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In addition, various plant Es differently affect the biofilm formation, so the method of preparation of Es should also be considered. 36,102 The results obtained for H. orphanidis suggested that AEs expressed low anti-biofilm activity compared to MEs and EEs, which was in conformity with the results obtained for antimicrobial activity. Es obtained from aerial parts were more effective than Es obtained from roots in the suppression of biofilm formation (Table 8).…”
Section: Discussionsupporting
confidence: 84%
“…QS signal molecules are the main participants of intercellular signaling pathway in which bacteria communicate and regulate gene expression by releasing small compounds called autoinducers into the environment when they reach a certain population density. Due to its role in regulatory processes and survival of bacteria, inhibition of QS systems by disrupting or interfering within these communications between bacterial cells, is an important target for developing novel anti-infective agents [34][35][36][37] . Some publications reported anti-QS activity of certain medicinal plants [38][39][40][41] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation